Strengthened Resilience: Impact of Pandemic in a Gawad Kalinga Community - Gallespen, Ervie Emelda; Villanueva, Marie Bernadette; Larido, Mariz; Deramas, Inna Isabel (JPAIR Multidisciplinary Research, 2021)
An educational institution that offers mostly paramedical courses has a significant role in strengthening community resilience as a recovery response to the Covid-19 pandemic. This study utilized a mixed-methods research design to describe the impact of the pandemic on the lives of 126 Gawad Kalinga community residents in Bacolod City, Philippines. The greatest impact of Covid-19 was the decrease in family income, but the resiliency of the residents was strengthened through each other’s support and that of partner institutions. There was difficulty in procuring food, medicine, and health care, but respondents declared their willingness to participate in livelihood initiatives. The following themes emerged from the interview with eight participants to validate the survey responses: Perseverance, Protection for Oneself and Others, Isolation, Better Safe than Sorry, Fear and Uncertainty, Weathering the Storm, Vaccines are Priority and Resiliency. Determining the impact of the pandemic was successful in incorporating the inputs of the residents into the community engagement programs of the partner educational institution. It is recommended that constant communication with the community and a regular assessment of their evolving needs must be monitored even beyond the pandemic. This can yield better recovery responses and health outcomes that may be adopted by other Gawad Kalinga communities all over the country.